Kemampuan Kawasan Nir-Konservasi dalam Melindungi Kelestarian Burung Endemik Dataran Rendah Pulau Jawa Studi Kasus di Kabupaten Kebumen - Sulistyadi, Eko (JURNAL BIOLOGI INDONESIA, 2010)
ABSTRACTCapability of Nir-Conservation Area for Preserving Jawa Lowland Endemic: CaseStudy in Kebumen District. Indonesia region is inhabited by 1.598 birds which 372 Indonesianendemic birds and 56 species of them are Jawa endemic. Amongs of jawa endemic birds, 19species are lowland occupant. Indeed the birds play important roles in ecosystem as agents ofpest population control, pollination, and seed dispersal. In lowland area of Jawa, intensivetransformation of land use exacerbated by no conservation area may threaten presence of theendemic birds. This study aims to assess caring capacity of disrupted area in low lands forpreserving endemic birds of Jawa.The study was conducted in Bedegelon river covering northern mountaneus area ofKebumen district from October-November 2007 using encounter rates methode. Survey wascarried out in three farm types: agroforestry (wanatani), intercropping agriculture area(tumpangsari) and mixed area of vegetation-settelment area (sempadan sungai).Result shows that four spesies Jawa lowland endemik birds was found in observed area.Lonchura leucogastroides and dicaeum trochileum found at all farm type, Prinia familiarisfound at intercropping agriculture area (tumpangsari). Alcedo coerulescens were observed atagroforestri area (wanatani) and mixed of vegetation-settelment area (sempadan sungai) farmtype.Key words : Jawa endemik birds, diversity, Jawa lowland, farm tipe, kebumen district